The Sultan of Vezirs : The Life and Times of the Ottoman Grand Vezir Mahmud Pasha Angeloviů (1453-1474) - Stavrides, Theoharis (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
Mahmud Pasha Angelovic served as Grand Vezir under Sultan Mehmed II, in the years following the Ottoman conquest of Constantinople, which were marked by an extensive imperial project, transforming the Ottoman principality into an empire. This book attempts to piece together the available evidence on Mahmud Pasha's Byzantine descent and family network, as well as his multi-faceted contribution to the founding of the new empire, through military leadership, diplomatic practices and architectural and literary patronage, considering also his execution and the creation of a posthumous legend presenting him as a martyr. Using Ottoman, Greek and Western sources, as well as archival material, this study focuses on the period of transition from Byzantine to Ottoman Empire and would be of interest to historians and other specialists studying that period.